SÍNTESE, CARACTERIZAÇÃO E AVALIAÇÃO ANTIBACTERIANA DE NOVOS COMPOSTOS ANFIFÍLICOS OBTIDOS A PARTIR DO CARDANOL - Lyvia Olarte de Moura (2023)
Moura, L.O. SYNTHESIS, CHARACTERIZATION AND ANTIBACTERIAL EVALUATION OF NEW AMPHIPHIC COMPOUNDS OBTAINED FROM CARDANOL [thesis]. Campo Grande: Institute of Chemistry, Federal University of Mato Grosso do Sul; 2023. Cardanol is a non-isoprenoid phenolic lipid derived from the liquid of cashew nutshell cashew nut shell liquid (CNSL) via distillation. Cardanol is an important starting material in the synthesis of novel compounds of biological and/or technical interest, due to its wide availability and inexpensive cost. Given the emphasis on using renewable and biodegradable materials, as well as the abundance of LCC in Brazil and the range of cardanol derivatives with varied applications, this study concentrated on synthesizing novel lipophilic molecules from cardanol. These chemicals, which fall into the categories of enaminones, chromones, and flavonoids, were tested for biological activity. Enaminones are important organic intermediate chemicals used in the synthesis of heterocyclic analogs and bioactive molecules. Chromones are oxygenated heterocycles with -pyrone rings; chromone and flavonoid derivatives, which are also found in flavones and isoflavones, have a variety of pharmacological actions. Chalcones, which are made up of unsaturated ketones connected to aromatic rings, have a wide range of biological appliocations, including antimalarial, anti-inflammatory, antiviral, antibacterial, antileishmanial, and fungicidal activities. The goal of this study was to synthesize and analyze lipophilic heterocycles derived from cardanol in order to examine their antibacterial properties. The synthetic method employed began with the synthesis of (ortho-hydroxy-4-pentadecyl) acetophenone from cardanol, followed by a series of derivatizations yielding chromones, enaminones, and chalcones. As a result, 1 new chromonic compound, 7 unique enaminones, and 7 chalcones, including 1 novel chalcone intermediate, were produced. Gram-negative bacteria such as E. coli and Klebsiella pneumoniae were tested, as well as Gram-positive bacteria such as Enterococcus faecalis and Staphylococcus aureus. Five compounds showed promising antibacterial activity against Enterococcus faecalis and Escherichia coli. Keywords: cardanol; CNSL; enaminones; chalcone; chromones.